PENGARUH MODEL PEMBELAJARAN KOOPERATIF STUDENT TEAM ACHIEVEMENT DIVISIONS (STAD) TERHADAP HASIL BELAJAR MATEMATIKA - Fatmawati, Yulia; Nasution, Syamsuddin Ali; Hadi, Syamsul (Universitas Djuanda, 2015)
The results obtained by the students are expected the goals of learning process. Feedback from students is processed through reflection and analysis during the learning process, so as to make improvements in the implementation of the next lesson. Lessons are conducted in the classroom for students, not only by memorizing facts and knowledge transfer, but also the students are challenged to find their own material to be learned by their own, so that learning actually useful perceived. The subject of Mathematics emphasizes reasoning in nature; instead emphasize the results of the experiment or observation results. Mathematics formed because human minds associated with ideas, processes and reasoning. Based on field observations indicate that there are still many students of Sukatani Elementary National School 4 in District Depok who earn math test scores below the KKM (Minimum completeness criteria). This condition is quite alarming and disturbing in view of the material on the comparison and scale is also an important material for controlled so that students achieve the competencies that have been defined. For that we need to use a learning model that is better than before. Various models of learning can be applied in teaching Mathematics; one of them is cooperative learning Student Team Achievement Divisions (STAD). The analysis of data in this study is to perform calculations in order to answer the formulation of the problem and to test the hypotheses that have been proposed. Due to the formulation of the problem and the hypothesis is directional influence, and then used to predict the dependent variable when the independent variables are known, then the data analysis by using simple regression and multiple regressions. Among assay instruments used were: 1). Tâ€test, 2). Simple Linear Regression, and 3). Analysis of Determination (R2). As for the coefficient determinant (KP) is formulated by KP = R2 x 100% or KP = R Square x 100%. Overall, the score of variable X (STAD model) amounted to 3021 with the highest score is 99 and the lowest is 70. Meanwhile, the scores obtained from variable Y (Student Results) is 2999 with the highest score of 100 and the lowest score 67. Based on the Model Summary Table it can be seen KP = R Square x 100% = 0.750 x 100% = 75%. This value indicates that the Cooperative Learning Model STAD contribute to Math Student Learning Outcomes of 75.0%, or it can be concluded Mathematics Student Learning Outcomes influenced by the Cooperative Learning Model STAD 75% while the remaining 25% are influenced by other factors which is not mentioned in this study, for instance: infrastructure, student motivation and so on. Finally, it can be concluded that cooperative learning model STAD affect the learning outcomes of students of Sukatani Elementary National School 4 in District Depok.